Sustainability Values of Students as Influences on the Image of a University Transitioning to Sustainability. - Mendiola, A.
The journey toward sustainability is a difficult process for a university given the complex requirements necessary for becoming sustainable. To implement sustainability initiatives effectively, therefore, it is important to obtain the support and commitment of university stakeholders. Having a good image as far as the school?s efforts at sustainability are concerned engages stakeholders and encourages that commitment. It is an important element of change as it provides evidence that the school is indeed serious in its activities. Yet is the perception of the school?s image influenced by the students? sustainability values? A survey of 798 college students at a private university in Metro Manila, Philippines was conducted to establish the relationship of the students? sustainability values as these influenced their perception of the university?s image. Structural equation modeling (SEM) with the EQS program was used to examine links between student sustainability values, perceptions of the impact of school initiatives, and school image. Results indicate that the school?s image as a contributor to sustainability is influenced by the perception students have of the long-term impact of school initiatives and the importance they place on environmental management. Such results highlight the need for creating awareness about, as well as encouraging involvement with, sustainability initiatives among students, especially with activities that have long-term horizons. Creating such a positive image through the route established by this research would help provide focus and efficiencies in the university?s sustainability initiatives.